United States Supreme Court Approach to First Amendment Freedom of Religion in Response to the COVID Pandemic - Swenson, Delaine Russell (Review of European and Comparative Law, 2021)
The 2020-21 Covid 19 Pandemic has raised many legal challenges as governments world-wide have struggled to deal with the public health and safety challenges of Covid. At the center of many of these decisions is the need to balance public health protections against other rights that have been infringed by legislation related to Covid Pandemic restrictions. One of the most important rights that have been implicated by Covid restrictions in the United States has been in the area of restrictions on religious worship which implicates the right to freedom of religion as enshrined in the United States Constitution. During the time of the Pandemic the United States Supreme Court, as the final arbiter of the United States Constitution has had to work to balance the interests of the government in protecting public health and safety with the right to freedom of religion. The Supreme Court’s approach to these cases reflects the difficulties inherent in balancing two such important interests in difficult circumstances and also represents the reality of the shifting majority in the Court as a result of new Justices appointed under the administration of Donald Trump. The Court has transitioned from a majority that opposed restrictions on governmental action during COVID to a majority that is more willing to stop governmental action that is deemed to be in violation of the Free Exercise of Religion Clause of the First Amendment.